The relationship between support staff's training strategies and preferred training needs of Pejabat Daerah dan Tanah Larut Matang, Taiping, Perak / Arifah Izzah Ahmad Sapuan - Ahmad Sapuan, Arifah Izzah (2013)
A research was conducted on support staff's training strategies and preferred training needs in Pejabat Daerah dan Tanah Larut Matang, Taiping, Perak (PDTLM). This study's objective was to identify the relationship between support staff's (NI 7) training strategies and their preferred training needs in government sector. The study was a non experimental nature because it described the relationships between variables. Support staff's in PDTLM Taiping, Perak had been given the questionnaires to be completed, where the research design for this study was a correlation between two variables. The overall results show that there is a relationship between preferred training needs and support staff's training strategies. Based on the research conducted, the researcher found that many sources of training strategies were found. The support staff's need self training which can improve their job performance and job skill when they attend training. Various suggestions were also made to improve the support staff's training strategies and training needs in government sector.